Colonial Britain’s Convict Labour Policies and the Cape Colony, 1806–1899 (Historia, 2022)
This article evaluates how convict labour alleviated labour shortages experienced in the Cape Colony from 1806 to 1899. It explores and evaluates Britain's significant impact on labour policies followed in the Cape Colony and focuses on the imperial government's role in developing legislation and procedures regarding management and transportation of convicts. It also considers the influence of nineteenth century policies of convict control in Britain, and the application of these policies and labour regimes in the Cape Colony. The article describes convict transportation, anti-convict agitation by Cape colonists and the economic significance of convict labour and public works projects. Finally, the convict lease system – the practice of hiring convicts to mines and to farmers – and Cape labour legislation's role in increasing the convict labour force through criminal sanctions will be examined.
Keywords: Convict labour; Cape Colony; anti-convict agitation; public works projects; mining companies